2015
DOI: 10.18632/oncotarget.4661
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-p21 activates endoplasmic reticulum stress and inhibits hepatocellular carcinoma

Abstract: LincRNA-p21 is a downstream long non-coding RNA (lncRNA) transcript of p53. LincRNA-p21 serves as a repressor in p53-dependent transcriptional responses and participates in diverse biological processes, including apoptosis, cell cycle, metabolism and pluripotency. However, the role of lincRNA-p21 in human hepatocellular carcinoma remains to be defined. Here in this work, we demonstrated that lincRNA-p21 acted as a tumor suppressive lncRNA in human hepatocellular carcinoma. We firstly found the downregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 32 publications
2
39
1
Order By: Relevance
“…Besides, ADAM10 is the target gene of miR‐122‐5p and the higher expression of ADAM10 is revealed in breast cancer tissue than that of normal tissue . A previous study demonstrated that lincRNA is closely linked with the development and progression of HCC . However, LINC01551 expression in HCC and its significance remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, ADAM10 is the target gene of miR‐122‐5p and the higher expression of ADAM10 is revealed in breast cancer tissue than that of normal tissue . A previous study demonstrated that lincRNA is closely linked with the development and progression of HCC . However, LINC01551 expression in HCC and its significance remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lnc-EGFR accelerates T-regulatory cell differentiation leading to immune evasion of HCC [6], and a variety of lncRNAs, such as MALT1 [7], TP73-AS1 [8], HULC [9], XIST [10], and HOTAIR [11], function as oncogenes, promoting HCC growth and metastasis by regulating miRNA or proteins. However, lncRNA uc.134 and lincRNA-p21 inhibit HCC progression by repressing CUL4A-mediated ubiquitination of LATS1 [12] or activating endoplasmic reticulum stress [13]. These findings indicate lncRNAs are potential prognostic factors for HCC.…”
Section: Introductionmentioning
confidence: 92%
“…LncRNA-p21 acts as a transcriptional suppressor in the p53 pathway by activating p53 to promote apoptosis [113]. It has been investigated that lncRNAp21 is deregulated in various human diseases, such as skin tumors, prostatic cancers, and HCCs [114][115][116]. It also functions as a tumor suppressor in malignancies, but the mechanism of the process remains elusive [115].…”
Section: Lncrnap21mentioning
confidence: 99%